Involvement of Small RNAs in Phosphorus and Sulfur Sensing, Signaling and Stress: Current Update - Kumar, Smita; Verma, Saurabh; Trivedi, Prabodh K. (Frontiers in Plant Science, 2017)
Plants require several essential mineral nutrients for their growth and development. These nutrients are required to maintain physiological processes and structural integrity in plants. The root architecture has evolved to absorb nutrients from soil and transport them to other parts of the plant. Nutrient deficiency affects several physiological and biological processes in plants and leads to reduction in crop productivity and yield. To compensate this adversity, plants have developed adaptive mechanisms to enhance the acquisition, conservation and mobilization of these nutrients under deficient or adverse conditions. In addition, plants have evolved an intricate nexus of complex signaling cascades, which help in nutrient sensing and uptake as well as to maintain nutrient homeostasis. In recent years, small non-coding RNAs such as micro RNAs (miRNAs) and endogenous small interfering RNAs (siRNAs) have emerged as important component in regulating plant stress responses. A set of these small RNAs have been implicated in regulating various processes involved in nutrient uptake, assimilation and deficiency. In response to phosphorus (P) and sulphur (S) deficiencies, role of small RNAs, miR395 and miR399, have been identified to be instrumental; however, many more miRNAs might be involved in regulating the plant response to these nutrient stresses. These small RNAs modulate expression of target genes in response to P and S deficiencies and regulate their uptake and utilization for proper growth and development of the plant. This review summarizes the current understanding of uptake, sensing and signaling of P and S and highlights the regulatory role of small RNAs in adaptive responses to these nutrient stresses in plants.